2010
DOI: 10.1007/s11430-010-4026-8
|View full text |Cite
|
Sign up to set email alerts
|

A shallow aftershock sequence in the north-eastern end of the Wenchuan earthquake aftershock zone

Abstract: Previous studies show that mature faults are filled with fault gouge in the shallow part and thus cannot accumulate enough strain energy for earthquakes. Therefore most earthquakes are deeper than 5 km, except those events occurring on new faults or in intact rocks. From field observation, Wenchuan earthquake is found to rupture the free surface about 200 km, but the rupture may extend underground much further from teleseismic body waves inversion and aftershocks distribution. In the northeastern end of the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…5d and 5e), which agrees with the near-field postseismic InSAR (Interferometric Synthetic Aperture Radar) observations that reveal short wavelength deformation across this fault segment (Huang et al, 2014). The shallow aftershocks also suggest that the shallow part of this segment was active under the loading of deep coseismic slip (Luo et al, 2010). Combined with this evidence, we infer that the stress on the Qingchuan segment might have been released (Fig.…”
Section: Seismic Hazard Assessment At the Extensions Of The Wenchuan supporting
confidence: 86%
“…5d and 5e), which agrees with the near-field postseismic InSAR (Interferometric Synthetic Aperture Radar) observations that reveal short wavelength deformation across this fault segment (Huang et al, 2014). The shallow aftershocks also suggest that the shallow part of this segment was active under the loading of deep coseismic slip (Luo et al, 2010). Combined with this evidence, we infer that the stress on the Qingchuan segment might have been released (Fig.…”
Section: Seismic Hazard Assessment At the Extensions Of The Wenchuan supporting
confidence: 86%
“…Recently, a study of the aftershock sequence of the 2008 Great Wenchuan earthquake also reported events shallower than 5 km in the northeastern tip of the Wenchuan earthquake rupture zone [6]. All these shallow earthquakes took place in the rigid rocks of Paleozoic strata or plutonic bodies, both of which are very strong and accumulate massive strain energy.…”
mentioning
confidence: 99%
“…Though depth phases such as sPL help to constrain focal depth well, but it is still affected by the velocity model used, though the depth error can be reduced to 1-2 km when a good velocity model is used (Chong et al, 2010;Luo et al, 2010;Wei et al, 2009). Another limitation of using sPL in constraining depth is that sPL can not be observed when SV wave happens to be near the nodal plane.…”
Section: Discussionmentioning
confidence: 99%